The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/bph.12813
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically distinct phenotypes of α1B‐adrenoceptors: variation in binding and functional affinities for antagonists

Abstract: BACKGROUND AND PURPOSEThe pharmacological properties of particular receptors have recently been suggested to vary under different conditions. We compared the pharmacological properties of the α1B-adrenoceptor subtype in various tissue preparations and under various conditions. EXPERIMENTAL APPROACH[ 3 H]-prazosin binding to α1B-adrenoceptors in rat liver (segments, dispersed hepatocytes and homogenates) was assessed and the pharmacological profiles were compared with the functional and binding profiles in rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…(systemic) administration of compounds and the additional role of pharmacokinetic factors (which cannot be completely ruled out in pithed rats). Consistent with these views, other studies performed in vivo with these compounds have also shown limited selectivity [ 31 ]. Notwithstanding, the pithed rat model is predictive of (cardio)vascular side effects [ 11 , 12 ] and provides information that cannot be obtained from in vitro studies [ 32 ].…”
Section: Discussionsupporting
confidence: 66%
“…(systemic) administration of compounds and the additional role of pharmacokinetic factors (which cannot be completely ruled out in pithed rats). Consistent with these views, other studies performed in vivo with these compounds have also shown limited selectivity [ 31 ]. Notwithstanding, the pithed rat model is predictive of (cardio)vascular side effects [ 11 , 12 ] and provides information that cannot be obtained from in vitro studies [ 32 ].…”
Section: Discussionsupporting
confidence: 66%
“…, ; Yoshiki et al . ). Briefly, the rat striatum was carefully cut into small pieces at 4°C, using a razor and fine ophthalmic scissors under a stereoscopic microscope.…”
Section: Methodsmentioning
confidence: 97%
“…At the end of the incubation with 50 nM [ 3 H]ACh for 20 min or 50 nM [ 3 H]choline for 10 min, 3 mL ice‐cold incubation medium was added and the segments were washed for 15–20 s. Finally, the segments were dissolved in 0.3 M NaOH, and the radioactivity and protein content were measured (Yoshiki et al . ). Nonspecific tissue accumulation of both radioligands was determined after incubation in the presence of 3 mM tetraethylammonium (TEA) for [ 3 H]ACh uptake or 3 mM hemicholinium‐3 (HC‐3) for [ 3 H]choline uptake (Muramatsu et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A number of "antagonists" have been shown to display hitherto unappreciated agonistic effects, for example, propranolol and carvedilol at the b 2 -adrenoceptor (Baker et al, 2003a;Wisler et al, 2007) and atropine at the muscarinic M 3 receptor (Stewart et al, 2010). Furthermore, there is no a priori reason why antagonists may not display differential affinities dependent on the pathway/effector system being monitored (Kenakin, 2014); propranolol has a 5-fold higher affinity to inhibit adrenaline-stimulated cAMP accumulation compared with CRE-SPAP transcription at the b 2 -adrenoceptor (Baker et al, 2003b), and even larger differences have been observed for a 1B -adrenoceptor antagonists (Yoshiki et al, 2014). The reason for multiple antagonist affinity states remains largely unknown, but it is possible that the residence time of ligands may contribute to differential signal pathway activation/ inhibition.…”
Section: Discussionmentioning
confidence: 99%